Expanded Criteria Donor With Severe Acute Kidney Injury: Worth to Use? - Thotsiri S. (2023)
Background: Expanded criteria donors (ECDs) may present with acute kidney injury (AKI). Many transplantation centers refuse to use these kidneys because of concerns about poor transplant outcomes, resulting in a high discard rate. However, long-term results of ECDs with AKI (ECDs + AKI) have not been extensively studied. Methods: We retrospectively compared outcomes of ECDs with ECDs + AKI. Primary outcome was 5-year allograft and patient survival rate. Secondary outcomes were allograft function, rates of delayed graft function, and allograft rejection. Results: Of 743 deceased donor kidney transplant recipients, 95 ECD cases were included in this study. There were 38 patients (40%) with ECDs and 57 patients (60%) with ECDs + AKI. Mean donor creatinine was progressively higher with severity of AKI. Five-year graft and patient survival were comparable between ECDs and ECDs + AKI (80.6% vs 81.1%, P =.95 and 91.7% vs 88.7%, P =.73). Mean (SD) allograft estimated glomerular filtration rate was 36.7 (14.5) vs 40.6 (22.7) mL/min/1.73 m2 with P =.61, respectively. Multivariate analysis showed factors associated graft loss were delayed graft function (P =.01) and donor-recipient age difference ≥10 years (P =.038), not AKI status. Conclusions: Kidney transplant from ECDs + AKI has comparable allograft survival with ECDs without AKI. Use of ECDs + AKI is worthwhile and kidneys from ECDs + AKI should not be discarded. Recipient selection and perioperative care are important to optimize the use of scarce resource.